Snakes of Sudan: New Locality Records and an Update - Mohammed A. A. Abdelhameed; Ismail E. Ahmed; Zuheir N. Mahmoud (Innovations in Biological Science Vol. 4, 2024)
Snakes of Sudan comprise 77 species, 36 genera and 12 families. Tricheilostomadissimilis and Telescopusgezirae (2.3%) are endemic and Myriopholismacrohyncha, Caususresimus, T. dissimilis, Eirenis africanus, Elapsoidealaticincta, Psammophissudanensisand T. geziraeare type locality (9.1%). The study added 36 new locality records and confirmed 33 collection sites. Eleven species are poisonous to man. The affinities of snakes of Sudan with the neighboring countries were quantified. Python regius and Python sebae are near threatened while the rest are at least concern. Poaching in the skin of Python spp. justifies their conservation.